2005
DOI: 10.17660/actahortic.2005.697.29
|View full text |Cite
|
Sign up to set email alerts
|

Lettuce Response to Leachate Recycling in an Arid Zone Greenhouse

Abstract: Lettuce response to salinity has been studied in open irrigation systems but not under solution recycling conditions. The objective of this study was to determine effects of threshold EC values for solution replacement on stalk weight and quality, solution chemistry and quantities of water and nitrogen removed from the system. Results showed that lettuce yield response to threshold EC in recycled solutions was similar to response to steady salinity in open irrigation systems reported in the literature. The sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The opposite results were obtained by Ahmed et al (2019) , who observed a gradual reduction in the water content in L. sativa roots and shoots with increasing NaCl concentration (2019). Many differences in the growth parameters of L. sativa grown under salt stress have been observed by various researchers (e.g., Bar-Yosef et al, 2005 ; Ünlükara et al, 2008 ; Kurunc, 2021 ). Presumably, the varieties of L. sativa are characterized by large differences in salinity tolerance, and plant responses may be related to other morphological and physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The opposite results were obtained by Ahmed et al (2019) , who observed a gradual reduction in the water content in L. sativa roots and shoots with increasing NaCl concentration (2019). Many differences in the growth parameters of L. sativa grown under salt stress have been observed by various researchers (e.g., Bar-Yosef et al, 2005 ; Ünlükara et al, 2008 ; Kurunc, 2021 ). Presumably, the varieties of L. sativa are characterized by large differences in salinity tolerance, and plant responses may be related to other morphological and physiological parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In a few articles detailed indications are given on the technical preparation and management of an experiment in SCS (Karam and Al-Daood, 2005;Marfà et al, 2005;Rouphael et al, 2005), but little information is available about the description of the experimental sizing (Frezza et al, 2005;Huber et al, 2005;Sato, 2005;Thompson et al, 1998). Only a few authors such as López-Galarza et al (2005) report indication about the suppliers, and some articles have details of the system also with the graphic scheme (Bar-Yosef et al, 2005;Karam and Al-Daood, 2005;Marfà et al, 2005).…”
Section: Information On Experimental Plants For Scsmentioning
confidence: 99%